Activation of Endoplasmic Reticulum Stress in Granulosa Cells from Patients with Polycystic Ovary Syndrome Contributes to Ovarian Fibrosis - Takahashi, Nozomi; Harada, Miyuki; Hirota, Yasushi; Nose, Emi; Azhary, Jerilee MK; Koike, Hiroshi; Kunitomi, Chisato; Yoshino, Osamu; Izumi, Gentaro; Hirata, Tetsuya; Koga, Kaori; Wada-Hiraike, Osamu; et al. (Scientific reports, 2017)
Recent studies report the involvement of intra-ovarian factors, such as inflammation and oxidative stress, in the pathophysiology of polycystic ovary syndrome (PCOS), the most common endocrine disorder of reproductive age women. Endoplasmic reticulum (ER) stress is a local factor that affects various cellular events during a broad spectrum of physiological and pathological conditions. It may also be an important determinant of pro-fibrotic remodeling during tissue fibrosis. In the present study, we showed that ER stress was activated in granulosa cells of PCOS patients as well as in a well-established PCOS mouse model. Pharmacological inducers of ER stress, tunicamycin and thapsigargin, were found to increase the expression of pro-fibrotic growth factors, including transforming growth factor (TGF)-β1, in human granulosa cells, and their expression also increased in granulosa cells of PCOS patients. By contrast, treatment of PCOS mice with an ER stress inhibitor, tauroursodeoxycholic acid or BGP-15, decreased interstitial fibrosis and collagen deposition in ovaries, accompanied by a reduction in TGF-β1 expression in granulosa cells. These findings suggest that ER stress in granulosa cells of women with PCOS contributes to the induction of pro-fibrotic growth factors during ovarian fibrosis, and that ER stress may serve as a therapeutic target in PCOS.